2006
DOI: 10.1007/s00381-006-0230-4
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial epidural hematoma of traumatic etiology in infants

Abstract: EDH in infants represents a life-threatening complication of head injury, which requires early identification and prompt surgical or conservative management depending on the patient's clinical condition, size of EDH, and presence of midline structure shift on head CT scan. Mortality and long-term morbidity are low with early diagnosis and prompt treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 26 publications
6
38
1
Order By: Relevance
“…This finding is in concordance with a study from Stockholm, which reported that falls were the predominant cause in children and even more often in younger children [13]. For infancy EDH, it has been widely shown that falls contribute most of the causes of injury [8,9]. Also for nonfatal unintentional head injuries, falls have been reported to be the leading cause in the infant population [14].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is in concordance with a study from Stockholm, which reported that falls were the predominant cause in children and even more often in younger children [13]. For infancy EDH, it has been widely shown that falls contribute most of the causes of injury [8,9]. Also for nonfatal unintentional head injuries, falls have been reported to be the leading cause in the infant population [14].…”
Section: Discussionsupporting
confidence: 88%
“…Beni-Adani’s [8] preliminary data suggested that TINS is useful for selecting patients for head CT scan and prediction of prognosis in infants with epidural hematoma (EDH). In concordance with Beni-Adani’s [8] report, a recent study on infants showed that patients who died of EDH had high TINS scores upon admission [9]. …”
Section: Introductionsupporting
confidence: 79%
“…Furthermore, the criteria for utilizing surgical evacuation vs conservative management have remained ill-defined. Thus, the lack of any guideline regarding the appropriate management of EDH in pediatric patients and particularly in infants makes the management of this specific group of patients all the more complicated (10).…”
Section: Khaled Chowdhury Smn Et Al: Extradural Haematoma In Childrenmentioning
confidence: 99%
“…It has been estimated that EDH represents 2-3% of all head injuries in the pediatric population (10). The mean age of pediatric patients harboring EDH is between 6 and 10 years and it is even rarer among infants under the age of 12 months (3,7,10,28).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, due to the pronounced increase in the number of patients who undergo brain CT scans following minor head injuries, we noticed profound changes in the clinical features of children with traumatic EDH, resulting in a greater proportion of EDH detected in patients who are still conscious and neurologically intact or with minimal symptoms [2, 3]. The aim of this study is to report the outcome after nonsurgical management in those children who remain in good clinical condition.…”
Section: Introductionmentioning
confidence: 99%